Visual essentialism & social kinds. (3rd August 2021) - Tullmann, Katie
Abstract: Scholars increasingly deny that they are strictly biological. Instead, these scholars argue that they are socially constructed. One challenge is to square the notion of social kinds with the apparent perception of those categories. I argue that we do not perceive social categories such as race. Instead, racial categories are visually encoded based on visible markers that are proxies for social kinds. Thus, I argue that the assumption of seeing social categories commits us to a flawed theory of visual essentialism : the idea that some social kinds are visible properties that are biologically determined.